2013
DOI: 10.3796/ksft.2012.49.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Dominant causes on the catch fluctuation of a set net fishery in the mid-south sea of Korea

Abstract: The annual and monthly fluctuation in the species composition and the catch abundance of dominant species were analyzed using the daily sales slip catch data by a set net in the offshore waters off Dolsan Island in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…25% of the annual fisheries production in South Korea, i.e., during the years 2010-2012 where they caused a roughly loss of US$68.2-204.6 million [66]. Moreover, the massive N. nomurai proliferation heavily reduced the catch stock in 2009 with a yielding an average loss of 100 ton of fish catch per month in eastern and southern Korea [67]. Moreover, envenomation events caused by jellyfish in this region have shown a marked increase in the last decade, from 2007 to 2019 the number of cases was four-fold higher [68,69], including a first fatal case caused by N. nomurai in 2012 [70], thus becoming a risk factor for tourism [71].…”
Section: Climate and Jellyfish Dynamics In The Korean Peninsulamentioning
confidence: 99%
“…25% of the annual fisheries production in South Korea, i.e., during the years 2010-2012 where they caused a roughly loss of US$68.2-204.6 million [66]. Moreover, the massive N. nomurai proliferation heavily reduced the catch stock in 2009 with a yielding an average loss of 100 ton of fish catch per month in eastern and southern Korea [67]. Moreover, envenomation events caused by jellyfish in this region have shown a marked increase in the last decade, from 2007 to 2019 the number of cases was four-fold higher [68,69], including a first fatal case caused by N. nomurai in 2012 [70], thus becoming a risk factor for tourism [71].…”
Section: Climate and Jellyfish Dynamics In The Korean Peninsulamentioning
confidence: 99%
“…The set net catches between Dolsan Island and Namhae Island in the Yeosu Bay vary greatly depending on the location of the fishing ground, net sizes, operating conditions and sea conditions (Cha, 2009;Kim, 1993;Kim & Rho, 1993, 1994, 1995, 1996Kim et al, 1988Kim et al, , 1989Kim et al, , 2013. The dominant fish species in the set net in our study was Spanish mackerel.…”
Section: Characteristics Of Fluctuations In Catch and Water Temperaturementioning
confidence: 67%
“…This indicates that the Tsushima Current are very influential on the inflow of Spanish mackerel into the Yeosu Bay's set net fishing grounds. According to Kim et al (2013) in the 2004-2011 survey of the catch and species composition of set nets at the southeastern Dolsan Island, Spanish mackerel predominantly accounted for approximately 70% of the total catch from summer to late autumn. Similarly, our study showed that the Spanish mackerel catch rate was high in summer and autumn.…”
Section: Characteristics Of Fluctuations In Catch and Water Temperaturementioning
confidence: 99%
“…, (Cha et al, 2001;Cha et al, 2004). (Cha, 1999;, (Cha et al, 2001;Cha et al, 2008), (Kim et al, 2003;Kim et al, 2013), (Ryu et al, 2005), (Cha et al, 2007;, (Cha, 2010) . , , (Gil et al, 2004), (Chun et al, 2009), (Lee, 2011), (Lee et al, 2008), (Beack et al, 2010), (Hong et al, 2008) .…”
mentioning
confidence: 99%